2015
DOI: 10.1155/2015/969040
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Osteoporosis in HIV/HCV Coinfected Patients: A Literature Review

Abstract: Vitamin D deficiency further increases the risk of osteoporosis in HIV-positive patients coinfected with hepatitis C virus (HCV); however, it is still unclear whether HCV-related increased fracture risk is a function of the severity of liver disease. The aim of this review was to identify studies on associative vitamin D deficiency patterns in high-risk populations such as HIV/HCV coinfected patients. We did this by searching MEDLINE and EMBASE databases, from inception to August 2014, and included bibliograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…of the main causes of liver disease and increases the risk of developing HCC by 2-6% per year (Oliviera-Andrade et al, 2009). Recent in vitro studies have shown that VD acts as an antiviral agent that inhibits HCV production in a human hepatoma cell line (DiCarlo et al, 2015). In patients with HCV that underwent liver transplantation with subsequent recurrent HCV, high rates of sustained virologic response were noted in patients receiving VDS (Abu-Mouch et al, 2011;Bitetto et al, 2011;Iruzubieta et al, 2014).…”
Section: Sustained Virologic Response Chronic Hcv Is Onementioning
confidence: 99%
See 1 more Smart Citation
“…of the main causes of liver disease and increases the risk of developing HCC by 2-6% per year (Oliviera-Andrade et al, 2009). Recent in vitro studies have shown that VD acts as an antiviral agent that inhibits HCV production in a human hepatoma cell line (DiCarlo et al, 2015). In patients with HCV that underwent liver transplantation with subsequent recurrent HCV, high rates of sustained virologic response were noted in patients receiving VDS (Abu-Mouch et al, 2011;Bitetto et al, 2011;Iruzubieta et al, 2014).…”
Section: Sustained Virologic Response Chronic Hcv Is Onementioning
confidence: 99%
“…Vitamin D (VD) has a number of pleiotropic effects including anti-inflammatory properties; antiapoptosis; antifibrosis; regulation of function in the kidney, heart, and immune system; and it maintains homeostasis by regulation of hormone secretion, cell proliferation, and differentiation (Lai & Fang, 2013). Research outlines the merits of VD supplementation (VDS) in patients with chronic liver disease (CLD) of various etiologies (Anty et al, 2014;DiCarlo et al, 2015;Eliades & Spyrou, 2015;Fernandez-Fernandez, Linares-Torres, Matias, Jorquera-Plaza, & Olcoz-Goni, 2015). Cited benefits can be stratified into areas such as the immune system (innate and adaptive), bone health, and all-cause mortality (Iruzubieta, Teran, Crespo, & Fabrega, 2014;Stokes, Volmer, Grunhage, & Lammert, 2013;Villar, Del Campo, Ranchal, Lampe, & Romero-Gomez, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains unclear whether lower vitamin D levels are associated with either decreased bone mineral density or increased fracture risk in the setting of HIV/HCV co-infection [49]. …”
Section: Introductionmentioning
confidence: 99%
“…These properties have been fully recognized, but a nontraditional role of vitamin D has also been reported in cancer and autoimmune disease [ 59 ], as well as in chronic liver disease and chronic hepatitis C patients, where vitamin D is involved in regulating the immune system, inflammatory response, and fibrogenesis [ 60 ].…”
Section: The Role Of Vitamin E and Vitamin D Supplementationmentioning
confidence: 99%